New human isolates of Trypanosoma cruzi confirm the predominance of hybrid lineages in domestic transmission cycle of the Argentinean Chaco - Macchiaverna, Natalia Paula (2018)
Trypanosoma cruzi, the etiological agent of Chagas disease, was initially classified into 6 Discrete Typing Units (DTUs). The hybrid DTUs TcV and TcVI are the most frequent in domestic transmission cycles throughout the Southern Cone countries of South America. Here, we genotyped parasite isolates from human residents in Pampa del Indio municipality, Chaco, to further characterize the structure of T. cruzi populations, and to assess the degree of overlapping between the domestic and sylvatic transmission cycles. Artificial xenodiagnostic tests were performed to blood samples from 125 T. cruzi-seropositive people (age range, 3–70 years) who represented 14.3% of all seropositive residents identified. Parasites were obtained from feces of T. cruzi-infected Triatoma infestans examined 30 or 60 days after blood-feeding, and grown in vitro. The cultured parasites were genotyped by means of two PCR-based protocols. DTUs were determined from 39 (31%) patients residing in 28 dwellings. The only DTUs identified were TcV (92%) and TcVI (8–36%). Households with more than one parasite isolate consistently displayed the same DTU. Further sequencing of a fragment of the TcMK gene from selected samples argue against the occurrence of mixed TcV-TcVI infections in the study population. Sequencing data revealed an unexpected degree of genetic variability within TcV including two apparently robust subgroups of isolates. Our results for human residents confirm the predominance of hybrid lineages (TcV and to a much lesser extent TcVI) and the absence of sylvatic genotypes (TcI and TcIII) in (peri)domestic transmission cycles in the Argentinean Chaco area.